46.6k views
0 votes
How do I solve (2x-y)(3x+y)

User Aldert
by
4.8k points

2 Answers

3 votes

Answer:


= 6x^2 - xy - y ^2\\

Explanation:


(2x - y)(3x + y) \\ 2x(3x + y) - y(3x + y) \\ 6x^2 + 2xy - 3xy - y^2 \\ = 6x ^2- xy - y^2

User Marcel B
by
5.3k points
2 votes

Answer:

6x^2 -xy - y^2

Explanation:

(2x-y)(3x+y)

FOIL

first: 2x*3x = 6x^2

outer: 2x*y = 2xy

inner: -y*3x = -3xy

last: -y^y = -y^2

Add these together

6x^2 +2xy-3xy - y^2

Combine like terms

6x^2 -xy - y^2

User Fczbkk
by
5.5k points